Effects of statins on plaque rupture assessed by optical coherence tomography in patients presenting with acute coronary syndromes: insights from the optical coherence tomography (OCT)-FORMIDABLE registry. (10th June 2017) - Gili, Sebastiano; Iannaccone, Mario; Colombo, Francesco; Montefusco, Antonio; Amabile, Nicolas; Calcagno, Simone; Capodanno, Davide; Scalone, Giancarla; Rognoni, Andrea; Omedè, Pierluigi; Ugo, Fabrizio; Cavallo, Erika; et al.
Abstract: Aims: Chronic pre-treatment with statins may reduce mortality and morbidity in patients experiencing acute coronary syndromes (ACS), but mechanisms accounting for these findings are not completely understood. Methods and results: The optical coherence tomography (OCT)-Formidable registry retrospectively enrolled 285 consecutive patients with ACS undergoing OCT in 9 European centres. Mean age was 60.4 ± 12.8 years, 148 (51.9%) patients had hyperlipemia, 45 (15.8%) diabetes mellitus and 142 (49.8%) presented with ST Segment Elevation Myocardial Infarction (STEMI). Patients were stratified according to statin prescription: 150 (52.6%) were on chronic pre-treatment with statins before ACS and were more likely to present with non-ST segment elevation acute coronary syndromes (NSTE-ACS) at admission (111, 74%) rather than STEMI, while the opposite was observed for patients not on statins. The primary end-point of ruptured plaque at OCT occurred significantly less frequently in the patients on chronic pre-treatment with statins [odds ratio (OR) 0.375, 95% confidence interval (CI) 0.185–0.759, P = 0.006]. The secondary end-point of thin-cap fibro-atheroma (TCFA) at any site was significantly less frequent in the statin group (OR 0.423, 95%CI 0.213–0.840, P = 0.014). No differences were observed for the secondary end-point of not-ruptured TCFA as the culprit lesion. Pre-specified sensitivity analysis was conducted according to the pattern of ACS: the reported differences were confirmed for NSTE-ACS patients, with a trend towards less plaque rupture and a significant reduction of TCFA at any site with statins, but not for STEMI. Conclusions: Chronic pre-treatment with statins is associated with a reduced prevalence of ruptured plaques in patients presenting with ACS, particularly in those with NSTE-ACS. Statins bear hence the potential to reduce morbidity during the acute phase of ACS.